Acute Effect of Selective Yogic Exercises on Brainstem Auditory Evoked Potentials in Stable Chronic Obstructive Pulmonary Disease Patients - Nembang, Penchha; Limbu, Nirmala; Thakur, Dilip; Subedi, Priza; Bhatta, Narendra (Journal of Karnali Academy of Health Sciences, 2025)
Background: Chronic obstructive pulmonary disease (COPD) is presently regarded as a multi-system disorder. A decrease oxygen transport to brain in these patients alters spontaneous brain activity. Yoga plays a vital role in complementary management of the disease. Brainstem auditory evoked potentials (BAEP) reflect neuronal activity along the auditory pathway up to the midbrain. Thus, we aimed to assess the effects of short-term yogic exercises in BAEP in stable COPD patients. Methods: This one group pretest – posttest observational study enrolled 50 stable patients with COPD. Steps of yogic exercises which included bhujangasana (snake pose), nadisodhana pranayama (alternate nostril breathing), swana pranayama (panting dog breathing) and ajapa-japa meditation (constant awareness of breathing) were taught to subjects by yoga instructor and given rest for 15 minutes. Then, BAEP latencies were recorded. After recording subjects performed the 20-25 minutes of yogic exercises as per the instructions, immediately after the completion, BAEP latencies were recorded. Thereafter, subjects were allowed to have rest for 10-15 minutes recording was done again. Results: Latency of BAEP wave I (1.78 ± 0.50 vs 1.99 ± 0.49 ms, p=0.006) and wave II (2.91 ± 0.32 vs 2.99 ± 0.30 ms, p=0.006) significantly decreased immediately after yoga, compared to baseline in right ear. Similarly, latency of wave II (2.77 ± 0.42 vs 2.92 ± 0.46 ms, p=0.005) and wave V (5.72 ± 0.32 vs 5.91 ± 0.37 ms, p=0.017) significantly decreased immediately after yoga, compared to baseline in left ear. However, latency of wave IV (5.51 ± 0.32 vs 5.34 ± 0.40 ms, p=0.042) increased significantly after the rest of 30 minutes, compared to immediately after yoga in right ear. Conclusions: Enhancement of neuronal transmission along the auditory pathway up to the midbrain was seen immediately after yogic exercises, which returned back to the baseline after 30 mins of rest.